1965
DOI: 10.1136/jcp.18.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in active `juvenile' cirrhosis

Abstract: SYNOPSIS Twelve patients with active 'juvenile' cirrhosis (active chronic hepatitis, 'lupoid' hepatitis) and six subjects with other types of portal or postnecrotic cirrhosis were submitted to percutaneous renal biopsy. In addition, renal function was assessed in all patients by measurement of the 24-hour endogenous creatinine clearance, maximal urinary osmolality after deprivation of water, 24-hour urinary protein excretion, and routine urine analysis.Renal function was not significantly abnormal in either gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Penner 5 has reported that two of 18 AIH patients were complicated with membranous glomerulonephritis accompanied by nodular deposits of immunoglobulins and complements on their glomeruli. Silva et al 6 reported in their study of 12 cases of lupoid hepatitis that seven patients showed mild renal histologic changes very similar to early lupus nephritis, although the findings of renal function tests and urine analysis were not significantly abnormal. Tsurui et al 7 have also reported a case of AIH associated with glomerulonephritis with granular deposits of C1q.…”
Section: Discussionmentioning
confidence: 93%
“…Penner 5 has reported that two of 18 AIH patients were complicated with membranous glomerulonephritis accompanied by nodular deposits of immunoglobulins and complements on their glomeruli. Silva et al 6 reported in their study of 12 cases of lupoid hepatitis that seven patients showed mild renal histologic changes very similar to early lupus nephritis, although the findings of renal function tests and urine analysis were not significantly abnormal. Tsurui et al 7 have also reported a case of AIH associated with glomerulonephritis with granular deposits of C1q.…”
Section: Discussionmentioning
confidence: 93%
“…Autoantibody‐positive chronic active hepatitis is well known to be associated with a wide variety of systemic disease 1 . Numerous pulmonary endocrine, haematological, renal and neurological manifestations are recognised 2‐4 .…”
Section: Discussionmentioning
confidence: 99%